A multi-layer energy modelling methodology to assess the impact of heat-electricity integration strategies: The case of the residential cooking sector in Italy. (1st March 2019) - Lombardi, Francesco; Rocco, Matteo Vincenzo; Colombo, Emanuela
Abstract: To support the ongoing transition towards smart and decarbonised energy systems, energy models need to expand their scope and predictive capabilities. To this end, this study proposes a multi-layer modelling methodology that soft-links (i) a stochastic bottom-up load curves estimation model, (ii) a technology-rich energy system optimisation model (Calliope) and (iii) a Multi-Regional Input-Output model (Exiobase v.3), and applies it to investigate the economic and environmental consequences entailed by a massive replacement of traditional gas-fired kitchens with induction kitchens within the Italian residential sector. Two scenarios are considered for the analysis: (i) business as usual (BAU, 2015 energy system configuration), and (ii) national energy strategy (SEN, configuration prospected in 2030). The results show how the intervention produces positive net effects on the primary energy balance of the energy sector only when sustained by adequate shares of renewables, as in the SEN (−1.5 TWh∙y −1 ); otherwise, increased operation of fossil-fuel plants offsets gas savings (BAU, +2 TWh∙y −1 ). Nonetheless, feedbacks on other productive sectors entail additional energy consumption and emissions, thus counterpoising positive effects obtained within the energy sector even in the SEN scenario. Still, higher renewables penetration reduces overall additional emissions from 2.07 Mton∙y −1 for BAU to 0.88 Mton∙y −1 for the SEN. Highlights: A multi-layer methodology to link energy models and input-output models is proposed. Italian electricity demand due to massive electrification of cooking devices is assessed. Change in the Italian power production mix is assessed based on Calliope energy model. The related economic/environmental implications are assessed with the Exiobase model.